Pentingnya Pendidikan Bagi Generas Muda Dalam Meningkatkan Kualitas Pendidikan - Ahmad Qadir; Khavin Edsyah Putra; Muhammad Fathir A; Putri Khairamulya R (Jurnal Pendidikan Indonesia, 2022)
In the Era of Society 5.0, it is closely related to the problem of the quality of education in Indonesia, which of course has a very impact on the younger generation. The problems experienced today are the low quality of education and low moral education which has great potential for the quality of education, especially among the younger generation, this can occur due to the low quality of teachers, the low welfare of teachers, and also the low level of equitable distribution of the education system that is currently implemented. We can see this from the lagging behind in education in Indonesia compared to other countries. The education system that we currently implement is not much different from the education system in other countries. The difference is that regarding the field practice that is currently implemented, there are many fundamental mistakes, of course, resulting in a gap between the objectives of the education system and its implementation. This of course makes the goal unattainable and resolved properly. This study aims to find out the problems of the education system in Indonesia and also the mistakes that often occur and the solution of problems that currently occur.